New Stirling-Type Approximations for the Gamma Function - Mahmoud, Mansour; Almuashi, Hanan; Mortici, Cristinel (Contemporary Mathematics, 2025)
This paper presents a set of new and precise Stirling-type formulas that approximate the Gamma function and provide associated sharp bounds. The proposed approximations are constructed using ratios of monic polynomials of even degree. In conclusion, an open question is raised regarding the general structure of such Gamma function approximations.